Edukasi Pencegahan Luka Tekan pada Anggota Keluarga yang Mengalami Immobilisasi - Tedy Tulak, Grace; Nasus, Evodius; Rahma, Hariyani Desia; Cristin, Kartika; Nada, Katrun; Rahmadani, Magfira Alya (PT.Mantaya Idea Batara, 2023)
Immobilized patients are at high risk of developing pressure sores. Efforts to prevent pressure sores should be carried out early since the patient has been identified as being at risk of developing pressure sores. This community service activity aims to increase the knowledge of family members of patients who experience immobilization in preventing pressure sores. This community service activity was carried out at the Benyamin Guluh Kolaka Hospital Neurology Polyclinic. The service method is carried out through education, discussion and question and answer. The results of this dedication were obtained by the enthusiasm of the patient's family and the patient's family who actively asked questions so that they were committed to caring for family members who were immobilized to prevent pressure sores on the patient's body. They said that their knowledge had increased after being given education by the service team.